2019
DOI: 10.1039/c8ta10989c
|View full text |Cite
|
Sign up to set email alerts
|

Correlating lattice distortions, ion migration barriers, and stability in solid electrolytes

Abstract: Strong correlations are observed between lattice distortions, thermodynamic stability, and limiting barriers for percolating ion migration in solid electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
128
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(144 citation statements)
references
References 71 publications
15
128
1
Order By: Relevance
“…Another advantage of antiperovskite is its extraordinary chemical diversity. Similar to perovskite, a variety of combinations of elements can be accommodated, while maintaining the simple structural topology, thereby offering an ideal situation to easily and fully characterize fast ionic transport 15 , 16 . A very recent study on Li 3 OCl indicated that the presence of hydroxide (OH – ), providing the composition of Li 3– x O 1– x (OH) x Cl, or ultimately Li 2 (OH)Cl 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage of antiperovskite is its extraordinary chemical diversity. Similar to perovskite, a variety of combinations of elements can be accommodated, while maintaining the simple structural topology, thereby offering an ideal situation to easily and fully characterize fast ionic transport 15 , 16 . A very recent study on Li 3 OCl indicated that the presence of hydroxide (OH – ), providing the composition of Li 3– x O 1– x (OH) x Cl, or ultimately Li 2 (OH)Cl 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The first feature proposed by Ceder et al is that the anion arrangement of body-centered cubic (bcc) provides the lowest migration barrier for Li-ion diffusion, rather than a close-packed (fcc or hcp) anion framework 27 . Antiperovskites host the bcc framework composed of A- and B-site anions 10 , 13 , 16 . The second feature is that polarizable anions can critically soften and flatten the cationic transport landscape, leading to lower activation energy and higher ionic conductivity 23 , 25 , 28 – 31 .…”
Section: Introductionmentioning
confidence: 99%
“…27(b) decreases the ionic conductivity. 216 The disadvantage Table 6 The ionic activation energy and conductivity calculated computationally for different possible cationic and anionic substitutions in LGPS structure. 205 Reproduced with permission from ref.…”
Section: Anti-perovskitementioning
confidence: 99%
“…Copyright (2018), Royal Society of Chemistry. (b) Different substitution that leads the ionic conductivity to decrease due to the distortions 216. Reproduced with permission from ref 216…”
mentioning
confidence: 99%
“…One of them is doping. [3][4][5][6][7] Recent studies show that the replacement of Fe 3+ (0.645 Å) by Cr 3+ (0.615 Å) reduces the lattice aspect ratio, increases the ferroelectricity, and suppresses the ion migration. [3][4][5] Layered compounds of Aurivillius phase have received considerable attention in recent years because of their fatigue-free ferroelectric property, lead-free composition, and high Curie temperature.…”
Section: Introductionmentioning
confidence: 99%